Evaluation of Antibacterial Activity of Some Algae Isolated from Waterfall Derna, Libya - Hanan Abobaker,; Najia Ibrahim,; Farag Shaieb, (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. The study demonstrated the antibacterial activity of crude freshwater algae extracts of five species (Chlamydomonas reinhardtii, Cladophora sauteri, Chlorella vulgaris, Ulothrix zonata and Nostoc piscine) isolated from waterfall Derna- Libya by using Agar well diffusion method. Methods. The antibacterial activity was tested in vitro against (Staphylococcus aureus, Bacillus sp., Streptococcus pyogenes, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Salmonella enterica, Xanthomoas axonopodis and Agrobacterium tumefaciens). Results. All algae species showed effects against different selected bacteria, C. vulgaris crude extracts showed that higher inhibitory effect against S. enterica, as for C. reinhardtii showed high effect against K. pneumoniae, while U. zonata showed higher effects against S. pyogenes. However, N. piscine showed high effect against S. pyogenes, and C. sauteri showed high effect against S. enterica. The zone of inhibition was compared with zone of inhibition produced by the standard antibiotic discs in the plate. Conclusion. Our finding suggests the possibility of using algae species as a source of natural antibacterial.